Penguatan Motorik Halus Melalui Kegiatan Cooking Class di TK Al-Amin Palur - Anis Fitria (Lembaga Pengembangan Kinerja Dosen, 2025)
The development of fine motor skills is one of the fundamental abilities nurtured in early childhood education institutions, in accordance with developmental achievement indicators. Therefore, the purpose of this study is to determine the influence of Cooking Class activities on children's fine motor skills during the pre-cycle, Cycle I, and Cycle II, as well as to understand how the implementation of Cooking Class activities can improve the fine motor skills of children aged 4-6 years at Al-Amin Kindergarten. The method used in this study is classroom action research, with a sample of 37 students. Data collection techniques involved observation sheets and documentation. The data analysis results showed an improvement in the fine motor skills of children aged 4-6 years through Cooking Class activities, starting from the observations conducted in the pre-cycle stage and increasing in each subsequent cycle. This can be seen from the scores obtained, starting from the pre-cycle to Cycle II. The average score increased from 34.56% in the pre-cycle, to 58.98% in Cycle I,and showed a significant improvement to 85.70% in Cycle II.